Tidal air exposure thresholds in seagrass survival: photodamage-antioxidant imbalance and anthocyanin accumulation associated with Enhalus acoroides zonation limits - Hu Li; Shuju Guo; Mengjie Zhang; Tie Zhang; Litao Zhang; Xingkai Che; Wenjie Yu; Jianguo Liu (Marine Pollution Bulletin, 2026)

Integrated biochar-iron amendment mitigates rice cadmium uptake via soil immobilization, iron plaque barriers, and microbial community restructuring - Meiling Xu; Tianyi Hu; Fangge Xu; Jing Che; Guobing Wang; Yepu Li; Qiao Xu; Xiaozhi Wang (Journal of Environmental Chemical Engineering, 2026)

Dynamics simulation on microstructural properties evolution of high-alkali coal slag in reducing conditions: The roles of alkali oxide, alkaline earth oxides, and iron oxide - Guowei Ma; Junyan Gu; Maoyun Luo; Chang’an Wang; Jiamiao Liu; Yonggang Zhao; Lin Zhao; Limin Wang; Wanzhu Wu; Hu Wang; Defu Che (Fuel, 2026)

Isolation and functional characterization of goose-derived lactic acid bacteria with growth-promoting and gut health benefits in Sanhua geese - Changsheng Jiang; Wenli Shi; Ji Chen; Weitao Wang; Dandan Fang; Wanji Zhan; Wei Zuo; Chuanyan Che; Ahmed H. Ghonaim; Mengmeng Jin; Qianqian Hu; Keli Yang; et al. (Food Chemistry, 2026)

Depth heterogeneity within surface soils substantially affects microbial abundance, diversity, and co-occurrence patterns - Guanyu Chai; Yuan Du; Zelin Wang; Kaifang Liu; Yuan Chi; Yi Duan; Shuo Ma; Xin Hu; Rongxiao Che; Jianxing Li; Wenjun Liu; Dong Liu (Journal of Soils and Sediments, 2026)

Corrigendum to “Hyperoside impairs mitochondrial respiration in chronic myeloid leukemia by promoting STUB1-mediated ubiquitination and degradation of NOX4” [Toxicology and Applied Pharmacology 511 (2026) 117795] - Hong Che; Bingjie Zhao; Wenjing Yi; Peijia Liu; Lian Hu (Toxicology and Applied Pharmacology, 2026)

Rapid recovery from starvation stress in low-temperature anammox system: extracellular polymeric substances protection and dissimilatory nitrate reduction to ammonium synergistically promote nitrogen metabolism recovery - Zhenchuan Nie; Yiwen Wang; Tao Ya; Tianqi Dang; Xuejiao Wang; Che Liu; Zunfang Hu; Xiaohui Wang (Bioresource Technology, 2026)

Reduced irrigation and phosphorus redistribution optimizes common vetch–mediated soil metabolic and microbial shifts suppress potato late blight - Ting Che; Shan Sun; Yilei Zhou; Chenxi Wu; Tingting Sun; Kangji Gao; Feng Hu; Huixin Li; Huijuan Zhang; Peiyi Zhao; Li Xu (Agriculture, Ecosystems & Environment, 2026)

RBSS-YOLOv8: multi-scale feature enhancement for high-density pig aggression detection - Longqin Xu; Shuyin Hu; Jinghui Yang; Zhuhong Che; Xuekai Gao; Huiyuan Pang; Tianyou Huang; Zhiyun Xu; Lichen Liang; Meng Cui; Shuangyin Liu (Computers and Electronics in Agriculture, 2026)

Prenylated dihydrostilbenoid derivatives from the aerial parts of Glycyrrhiza uralensis and their potent antibacterial activity against drug-resistant clinical isolates - Yuxuan Zhong; Junfei Zhou; Shanwei Hu; Mengting Wang; Jingyu Liu; Jicong Du; Jin-Ao Duan; Hongkai Bi; Ming Zhao; Chun-Tao Che (Phytochemistry, 2026)

Intramolecular internal electric field and activated n-π* electronic transition co-promoted photocatalysis activity of carbon nitride: Mechanism and toxicity evaluation - Yanbin Chen; Tianyu Zhou; Chunbo Liu; Bo Hu; Guojie Liu; Guangbo Che (Journal of Environmental Sciences, 2026)

Characterization of the chemical constituents changes in Amomum tsao-ko during different storage periods using ultra-fast gas phase electronic nose and UHPLC-Q exactive HF-X - Mengmeng Hu; Shen Zhuang; Yi Zhao; Yanyun Che; Yunpeng Fan (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Effects of the foliar application of selenite at different growth stages on selenium transformation, silage quality and the metabolome of tiger nut (Cyperus esculentus L.) - Kexin Wang; Ting Gong; Xinge Du; Wei Liu; Ruize Sun; Chenghao Che; Yilin Zou; Shengnan Sun; Linlin Mei; Guofu Hu (Food Chemistry, 2026)

Spatiotemporal evolution and ecological risk assessment of heavy metals in agricultural black soils of Northeast China - Tianhao Che; Boling Deng; Naiwen Hu; Meixuan Wu; Hongwen Yu; Jing Yue; Quanying Wang (Environmental Research, 2026)

The state of knowledge for engineering with nature: Vegetation as wave buffer - Xifen Chen; Zhan Hu; Tori Tomiczek; Che-Wei Chang; Dan Cox; Maria Maza; Nobuhito Mori; Siddharth Narayan; Sungwon Shin; Tomohiro Suzuki (Coastal Engineering, 2026)

Estimating aerosol scattering hygroscopic growth factors at ambient relative humidity based on machine learning - Can Xia; Junying Sun; Xinyao Hu; Hongfei Tong; Xiaojing Shen; Yangmei Zhang; Quan Liu; Lei Liu; Jiayuan Lu; Huizheng Che; Xiaoye Zhang (Atmospheric Pollution Research, 2026)

A secreted alpha-amylase effectively induces reproductive cyst formation both within and across Colpoda species, key soil-dwelling protists - Zixin Cheng; Zhongqiao Song; Kejia Fu; Yuan Wang; Kai Chen; Jing Zhang; Che Hu; Xiaocui Chai; Shuai Luo; Fang Zhou; Yuan Xiao; Zhenfei Xing; et al. (Science China Life Sciences, 2026)

Daidzein alleviates high-alkalinity stress-induced inflammatory liver injury in common carp by modulating gut microbiota and hepatic metabolic reprogramming - Xinchi Shang; Meiqi Xing; Xinghua Che; Shiyu Hu; Haijun Wei; Xiaodan Shi; Lanlan Zhang; Wei Xu; Longwu Geng (Aquaculture, 2026)

Time-dependent mechanical response of buried water pipelines to cold waves under coupled multiphysics loading - Olawale Ayinde; Fei Wang; Qunfang Hu; Delu Che; Hongyan Ji; Guanfeng An (Tunnelling and Underground Space Technology, 2026)

Hyperoside impairs mitochondrial respiration in chronic myeloid leukemia by promoting STUB1-mediated ubiquitination and degradation of NOX4 - Hong Che; Bingjie Zhao; Wenjing Yi; Peijia Liu; Lian Hu (Toxicology and Applied Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Full-scale experimental study of flame behavior and thermal distribution in utility tunnel fires - Xiaojiang Liu; Zhao-Dong Xu; Jun Dai; Jiayu Che; Zhong-Wei Hu; Defu Che (Tunnelling and Underground Space Technology, 2026)

A positive feedback loop between the lncRNA TaHTMAR and TaHGSNAT is essential for thermo-sensitive male fertility in wheat - Xiaoran Gao; Qiang Geng; Xin Che; Fuqiang Niu; Jinke Liu; Lingling Hu; Xiaoxia Wang; Xiyue Song; Lingli Zhang (Plant Science, 2026)

Built-in electric field constructed by asymmetric electron cloud distribution for facilitating photocatalytic H2O2 production in covalent organic frameworks - Chuanxue You; Yue Zhou; Meiting Yang; Jingyang Li; Bo Hu; Yunchao Ma; Linlin Liu; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Deposition characterization and predictive modeling of phosphorus and heavy metals during sewage sludge incineration - Qianqian Guo; Taojie Duan; Yanjun Hu; Long Jiao; Lingqin Zhao; Fan Yu; Xu Wang; Lei Che; Frederik Ronsse (Journal of Environmental Management, 2026)

Mechanosensor YAP orchestrates human neural rosette morphogenesis via TEAD4-LEF1 transcriptional nexus - Jinghao Hu; Zan He; Huifang Hu; Xiaoyan Sun; Shanshan Che; Shuhui Sun; Miyang Ma; Yixin Zhang; Shuai Ma; Weiqi Zhang; Juan Carlos Izpisua Belmonte; Guoguang Zhao; et al. (Science China Life Sciences, 2026)

Molecular identification and characterization of a ‘Candidatus phytoplasma australasiaticum’ -related strain associated with Scaevola taccada virescence disease in China - Hai-Yan Che; Mei-Jiao Hu; Hai-Bo Long; Da-Quan Luo; Shao-Shuai Yu (Physiological and Molecular Plant Pathology, 2026)

Mo-doped NiCo-LDH@Ti3C2Tx-N MXene heterostructures for coin cells and 3D-printed wearable micro-supercapacitors - Jiayi Shen; Mai Li; Haotian Hu; Yifeng Cheng; Ayesha Irfan; Chenxi Li; Qinglin Deng; Limin Wu; Renchao Che (Chemical Engineering Journal, 2026)

A machine learning-based model for aerosol scattering hygroscopic growth factor (f(RH)) prediction in Beijing urban area - Hongfei Tong; Xinyao Hu; Can Xia; Xiaojing Shen; Yangmei Zhang; Quan Liu; Lei Liu; Linlin Liang; Jiayuan Lu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2026)

Mid‐to‐late Holocene climatic changes in the Eastern Mediterranean region: Speleothem‐based high‐resolution isotope record from Dim Cave, southern Türkiye - Mehmet Oruç Baykara; Mehmet Özkul; Chuan‐Chou Shen; Ezgi Ünal İmer; Horng‐Sheng Mii; Hsun‐Ming Hu; Chung‐Che Wu; Sándor Kele; Attila Demény (Journal of Quaternary Science, 2026)
Human–environment interactions have been affected by sudden climate changes in the Eastern Mediterranean region for thousands of years. Recent studies project a 20% decrease in precipitation by the end of this century compared to the 20th century. Therefore, high‐resolution paleoclimate data are needed to develop robust future climate projections and modeling studies for the Eastern Mediterranean. This study investigates the mid‐to‐late Holocene paleoclimatic shifts and their impacts on civilizations in the Eastern Mediterranean using high‐resolution isotope records from the Dim‐3 stalagmite (Dim Cave, southern Türkiye). A precise and robust age–depth model was constructed using 23 U/Th dating results, spanning from 4149 to 996 years (yr) BP. The isotope results show the driest conditions occurring at 3986 yr BP, with a rapid shift to wetter conditions after 3890 yr BP. These wetter conditions were followed by a prolonged dry period from 3280 to 2720 yr BP. A subsequent wet period between 2720 and 2228 yr BP was interrupted by a 698‐year growth hiatus in the stalagmite. In the final section of the record (1530–972 yr BP), initially wet climatic conditions transitioned to drier periods around 1425 yr BP and again between 1150 and 1075 yr BP. The Dim‐3 isotope record shows enriched isotopic values between 4140 and 3890 yr BP, coinciding with the “4.2 ka drying event.” While a brief humid period was observed between 3050 and 2920 yr BP, the overall isotope values show an enriched trend from 3250 to 2800 yr BP, indicating the imprint of the 3.2 ka and Bond 2 events.

Quantifying the sources of REE in the deep Philippine Sea: Insights from numerical modeling and field observations - Hong Che; Yi Zhong; Wenkai Guan; Qian Liu; Panfeng Li; Xue Ding; Bangqi Hu (Progress in Oceanography, 2025)

Lattice Boltzmann simulation on adsorption of sulfuric acid vapor by ash particles - Jiyun Ren; Chongjun Jiang; Fangfang Hu; Hui Wang; Yunhao Shao; Xinyu Liu; Zhang Wu; Feng Pan; Qidong Yang; Lei Deng; Defu Che (Fuel, 2025)

Cell-supporting cytoskeletons and phagocytic acquisition of compatible solutes emerge as common strategies for high-salt adaptation in different ciliates - Fengchao Li; Wenying Zhang; Shuai Luo; Ning Ma; Jing Zhang; Weiwei Qin; Che Hu; Xinxin Gao; Yuan Xiao; Chuanqi Jiang; Xiaocui Chai; Qiukun Wang; et al. (Science China Life Sciences, 2025)

Climate teleconnections among the Earth’s three poles - Anmin Duan; Xin Li; Wenting Hu; Tao Che; Jun Hu; Yuzhuo Peng; Chao Zhang; Die Hu; Yuheng Tang; Zhulei Pan; Qilu Wang; Guoxiong Wu (Science Bulletin, 2025)

A lightweight method for apple disease segmentation using multimodal transformer and sensor fusion - Yihong Song; Manzhou Li; Zizhe Zhou; Jiahe Zhang; Xiangge Du; Min Dong; Qinhong Jiang; Che Li; Yuantao Hu; Qiulin Yu; Dongmei Wang; Hegan Dong; et al. (Computers and Electronics in Agriculture, 2025)

Mapping snow cover frequency at 30 m for studying seasonal variations and topographic controls on the Tibetan Plateau - Guigang Wang; Tao Che; Liyun Dai; Yanxing Hu; Jun Wu; Saiyao Meng; Chuilei Kong; Jing Wang; Dongdong Feng; Shijie Wang; Xuemei Li (Journal of Hydrology, 2025)

Study on the mechanism of multiple sodium salts co-loading on ash fusibility and mineral evolution behaviors - Hongli Liang; Jinhao Yi; Yang Yang; Lei Zhang; Tao Ma; Weibin Chen; Hu Liu; Defu Che (Fuel, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Graft-modified amphiphilic dendron/polyimide regular through-pore composite membranes for oil/water separation - Chien-Chieh Hu; Cai-Syuan Sung; Ru-Jong Jeng; Chien-Hsin Wu; Ying-Chi Huang; Huai-Che Chang; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

Carbon nitride featuring a robust built-in electric field with ultra-high photocatalytic activity - Yue Xu; Tianyu Zhou; Wei Jiang; Bo Hu; Chunbo Liu; Guangbo Che (Chemical Engineering Journal, 2025)

Complex networks reveal teleconnections across cascading floods in the Yangtze River Basin - Fengyun Sun; Alfonso Mejia; Sanjib Sharma; Peng Zeng; Yi’na Hu; Kai Yang; Yue Che (Natural Hazards, 2025)

Improving underground pipeline resilience: Prediction and interpretability analysis of urban water distribution network pipe failures during cold waves using machine learning - Qunfang Hu; Delu Che; Qiang Zhang; Jiahua Zhou; Fei Wang; Zongyuan Zhang; Zhaoyang Song (Tunnelling and Underground Space Technology, 2025)

Microbial interactions of floc and biofilm sludge in PN/A processes in anaerobic/aerobic/anoxic mode: Competition or cooperation? - Yan Zhang; Jiaao Wang; Meina Hu; Tao Ya; Che Liu; Lingzhi Feng; Xiaohui Wang (Journal of Water Process Engineering, 2025)

Self-regulatory mechanisms of anammox system in response to CuO nanoparticles revealed by microbial ecological networks and metagenomics - Gengyi Zhang; Mei Hu; Xuejiao Wang; Che Liu; Tao Ya; Xiaohui Wang (Bioresource Technology, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

Chitosan/Gelatin/Carrageenan as a Composite Scaffolding Material for Cartilage Tissue Engineering - Chengyao Wang; Weiqin Zhao; Ning Ma; Linyu Chen; Jiajun Lu; Shuang Liu; Ziyi Wang; Huiju Hu; Hong Sun; Pengcheng Che (Journal of Medical and Biological Engineering, 2025)

Insight into VOCs source profiles by machine learning: Role of commonalities in synergistic pollution controls - Shuwei Zhang; Song Gao; Bo Wang; Zhukai Ning; Lingning Meng; Ming Hu; Xiang Che; Zheng Jiao (Journal of Hazardous Materials, 2025)

Dual-pathway photosynthesis H2O2 realized by carbon nitride with strong built-in electric field and awakened n-π* electron transition: Based on theoretical calculation guidance - Yuhan Yan; Tianyu Zhou; Chunbo Liu; Bo Hu; Guangbo Che (Chemical Engineering Journal, 2025)

Buprofezin causes early developmental toxicity of zebrafish (Danio rerio) embryos: morphological, physiological and biochemical responses - Shuting Qiang; Yufeng Che; Mingyang Lu; Yuan Tian; Lin Gao; Jingwen Chen; Tingzhang Hu (Aquatic Toxicology, 2025)

Deep Hypothermic Low Flow Results in Multiple Aspects of Neurological Deficits in Mice by eEF2 Hyperphosphorylation - Yumei Liao; Dongyang Che; Peng Liu; Xinyu Wang; Yanlin Zhang; Lingling Guo; Jinlin Hu; Tianyao Li; Mei Fong Lam; Nan Ma; Shiqing Zhang; Hua Lu; et al. (Molecular Neurobiology, 2025)

Mechanisms of corrosion and corrosion scale formation in water supply networks: A review - Qunfang Hu; Jiahua Zhou; Zhan Su; Shuang Nie; Fei Wang; Zongyuan Zhang; Qiang Zhang; Delu Che (Journal of Water Process Engineering, 2025)

Tailoring C-defect O-doping and n-π* transition awakened porous ultra-thin carbon nitride for efficient peroxymonosulfate activation: Performances and mechanism insight - Meng Tai; Guangbo Che; Tianyu Zhou; Honghui Teng; Chunbo Liu; Bo Hu (Journal of Environmental Sciences, 2025)

Nitrogen-rich carbon nitride activated peroxymonosulfate for the efficient photodegradation of 2, 4-dichlorophenol: Performance and mechanism insight - Tianyu Zhou; Siyi Wang; Meng Tai; Juan Du; Dongshu Sun; Guangbo Che; Linlin Liu; Chunhong Ma; Bo Hu (Environmental Research, 2025)

Land degradation decreased crop productivity by altering soil quality index generated by network analysis - Ming Gao; Wei Hu; Xingyi Zhang; Meng Li; Yongsheng Yang; Renfeng Che (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Eco-friendly lamellar structured graphene oxide-Lysine nanocomposite membranes with varying d-spacing for enhanced pervaporation desalination - Shalligito Habetamu Abebe; Hannah Faye M. Austria; T.M. Subrahmanya; Huai-Che Chang; Tsung-Han Huang; Gabriel V. Carballo; Wei-Song Hung; Chien-Chieh Hu; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

A two-stage hybrid model for dissolved oxygen prediction and control in aquaculture - Ziang Chen; Huiting Hu; Shuangyin Liu; Zhuhong Che; Xinmiao Wang; Zhuhua Hu; Tonglai Liu; Meng Cui; Longqin Xu (Aquaculture International, 2025)

A highly sensitive fluorescent probe based on functionalised ionic liquids for timely detection of trace Hg2+ and CH3Hg+ in food - Siying Che; Yao Fan; Xuemei Hu; Linlin Yin; Haiyan Fu; Yuanbin She (Food Chemistry, 2025)

XR-based interactive visualization platform for real-time exploring dynamic earth science data - Xuelei Zhang; Hu Yang; Chunhua Liu; Qingqing Tong; Aijun Xiu; Lingsheng Kong; Mo Dan; Chao Gao; Meng Gao; Huizheng Che; Xin Wang; Guangjian Wu (Environmental Modelling & Software, 2025)

Hydrodynamic Modelling of Severn Bore and Its Dependence on Ocean Tide and River Discharge - Bowen Che; Hao Hu; Jun Ma; Dongfang Liang (Journal of Marine Science and Engineering, 2024)
Owing to the high tidal range, the Severn Estuary and Bristol Channel have the potential to generate huge amounts of renewable electricity for the UK. During the flood tide, the surging water travels upstream to form the Severn Bore. This study explores the dynamics of the Severn Bore through hydrodynamic modelling, analyzing how the tidal amplitude, mean water level, and river discharge affect the bore’s intensity, reach, and sustainability. The Delft3D simulations show that the downstream tidal amplitude plays a critical role. Tides with an amplitude of less than 6 m will lead to the disappearance of the Severn Bore. The mean water level also significantly influences the bore’s propagation, with a 1.5 m drop resulting in a 15 km retreat of the bore. A high river discharge rate weakens the bore’s intensity and reduces its reach. These findings underscore the need for careful planning in tidal energy development within the Severn Estuary. Excessive exploitation of tidal energy can be detrimental to the Severn Bore and the ecological function of the estuary.

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Mesenchymal Stem Cells Overexpressing FGF21 Preserve Blood-Brain Barrier Integrity in Experimental Ischemic Stroke - Phuong Thao Do; De-Maw Chuang; Chung-Che Wu; Chi-Zong Huang; Yen-Hua Chen; Shuo-Jhen Kang; Yung-Hsiao Chiang; Chaur-Jong Hu; Kai-Yun Chen (Translational Stroke Research, 2024)

A surrogate model-based ESM parameter tuning scientific workflow management framework for HPC - Liang Hu; Xianwei Wu; Xilong Che (Earth Science Informatics, 2024)

Organic carbon decomposition temperature sensitivity positively correlates with the relative abundance of copiotrophic microbial taxa in cropland soils - Yuan Du; Anlan Yu; Yuan Chi; Zelin Wang; Xinrui Han; Kaifang Liu; Qiuping Fan; Xin Hu; Rongxiao Che; Dong Liu (Applied Soil Ecology, 2024)

Analyzing the effects of extreme cold waves on urban water supply network safety: A case study from 2020 to 2021 - Qunfang Hu; Delu Che; Fei Wang; Lei He (Urban Climate, 2024)

Influence of sources and atmospheric processes on metal solubility in PM2.5 in urban Guangzhou, South China - Zhisheng Zhang; Jun Tao; Leiming Zhang; Bangkai Hu; Ming Liu; Fuli Nie; Haitao Lu; Laiguo Chen; Yunfei Wu; Duohong Chen; Boguang Wang; Huizheng Che (Science of The Total Environment, 2024)

Construction and characterization of different hemolysin gene deletion strains in Vibrio parahaemolyticus (ΔhlyA, ΔhlyIII) and evaluation of their virulence - Jinyuan Che; Shaojie Hu; Qitong Fang; Binghong Liu; Zhuochen Liu; Cunjie Hu; Lei Wang; Lekang Li; Baolong Bao (Journal of Invertebrate Pathology, 2024)

Fluorinated Polyimides incorporated with heterogeneous ZrO2@KNbO3 as multiple carrier transport barriers for Ultra-High energy storage - Yao Su; Yuxin Jia; Dengwei Hu; Shilei Zhu; Xin Yang; Xiuzi Che; Yuanbiao Gong; Yongbo Fan; Weijia Wang; Huiqing Fan (Chemical Engineering Journal, 2024)

Experimental investigation on product and temperature distribution in a continuous flow packed-bed reactor for dodecahydro-N-ethylcarbazole dehydrogenation - Jingwen Xue; Pengzhao Li; Pengfei Yu; Jinhao Yi; Tao Ma; Hu Liu; Defu Che (Chemical Engineering Journal, 2024)

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

Sedimentation and transformation of heavy metals during the transport from the Yellow River estuary to the sea: Evidence from surface sediments of the Yellow River subaqueous delta - Caiping Hu; Ming Liu; Yiping Li; Jia Li; Xinying Che; Hongwei Wang (Marine Pollution Bulletin, 2024)

Multi-targets detection via combination of multi-stimulus-response engineered bacteria and hydrogel-based separation platform - Huachao Che; Xike Tian; Yulun Nie; Yong Li; Liqiang Lu; Yuguang Hu (Journal of Hazardous Materials, 2024)

Highly-separated Co anchored on S, O-doped carbon nitride for enhanced peroxymonosulfate activation: Insights into radical and non-radical pathways - Yuhang Deng; Simiao Wang; Tianyu Zhou; Bo Liu; Bo Hu; Liang Wang; Chunbo Liu; Wei Jiang; Guangbo Che (Chemical Engineering Journal, 2024)

Factors influencing mangrove carbon storage and its response to environmental stress - Chuanyi Guo; Pei Sun Loh; Jianxiong Hu; Zengxuan Chen; Siriporn Pradit; Chantha Oeurng; Ty Sok; Che Abd Rahim Mohamed; Choon Weng Lee; Chui Wei Bong; Xixi Lu; Gusti Z. Anshari; et al. (Frontiers in Marine Science, 2024)
Mangrove forests serve as significant carbon sinks and play a crucial role in mitigating climate change. Currently, the response of mangroves to intensified climate change and human activities, and the factors that influence the magnitude of carbon storage in their sediments remain uncertain. To address these questions, two sediment cores were collected from the mangrove reserve in Pearl Bay, Guangxi, China. The activity of 210 Pb in the sediment, grain size, bulk elemental composition, stable carbon isotopes, lignin, and different sediment organic matter (OM) fractions were investigated to determine the local mangrove’s response to climate change and human activities, as well as the factors influencing its carbon storage. The results showed mangrove forests with lower tidal ranges, slower sedimentation rates, and where OM predominantly originated locally tend to have larger carbon stocks. The mangrove OM (MOM) decreased progressively from the bottom to the top of the cores, indicating that the mangroves in Pearl Bay have possibly undergone degradation, which was further substantiated by the decrease in lignin content. Based on these results, the entire cores were divided into two stages: stable stage 1 (1963–2001) and degradation stage 2 (2001–2020). The cause of the mangrove degradation is likely due to the impact of human activities; however, these impacts are anticipated to gradually lessen in the future due to mangrove protection policies. Our results indicate that lignin can track and predict mangrove growth trends and provide guidance for the sustainable management of mangrove ecosystems.

Effects of sulfate on survival, osmoregulation and immune inflammation of mud crab(Scylla paramamosain) under low salt conditions - Yun Hu; Gao Gao; Kangxiang Qin; Xiaosong Jiang; Chenxi Che; Yuntao Li; Changkao Mu; Chunlin Wang; Huan Wang (Aquaculture, 2024)

Environmental impacts and decarbonization pathways of oily sludge pyrolysis based on life cycle assessment - Longtao Ji; Dungang Gu; Bin Cai; Lei Che; Lishan Xiao; Dominic C.Y. Foo; Nan Zhang; Yuhang Lou; Tingting Hu; Guanghui Li; Jiaqi Lu (Journal of Cleaner Production, 2024)

Unraveling novel umami peptides from yeast extract (Saccharomyces cerevisiae) using peptidomics and molecular interaction modeling - Chunyu Gao; Rilei Yu; Xiaomei Zhang; Xue Song; Lizhi Che; Yuying Tang; Jinyue Yang; Jing Hu; Jian Xiong; Xue Zhao; Hongwei Zhang (Food Chemistry, 2024)

4-tert-Butylphenol impairs the liver by inducing excess liver lipid accumulation via disrupting the lipid metabolism pathway in zebrafish - Huiyun Wang; Juan Liu; Shuting Qiang; Yufeng Che; Tingzhang Hu (Environmental Pollution, 2024)

Metaphire guillelmi exhibited predominant capacity of arsenic efflux - Xiayun Zang; Mingyue He; Yuanzhou Xu; Ting Che; Fei Wang; Jingjing Xu; Huijuan Zhang; Feng Hu; Li Xu (Chemosphere, 2024)

Dynamic constrained multi-objective optimization algorithm based on co-evolution and diversity enhancement - Wang Che; Jinhua Zheng; Yaru Hu; Juan Zou; Shengxiang Yang (Swarm and Evolutionary Computation, 2024)

Differential expression and bioinformatics analysis of proteins in response to NaCl stress in purslane - Hongmei Du; Shah Zaman; Fiza Liaquat; Shuiqingqing Hu; Muhammad Farooq Hussain Munis; Shengquan Che (South African Journal of Botany, 2024)

Accurate and precise in situ determination of beryllium contents in beryllium minerals using ablation spot size of 13 μm by LA–ICP–MS - Wen-Kai Jin; Xu-Dong Che; Ru-Cheng Wang; Huan Hu; Can Rao; Wen-Lan Zhang; Xiao-Feng Li (Journal of Geochemical Exploration, 2024)

Non-radical activation of persulfate with Bi2O3/BiO1.3I0.4 for efficient degradation of propranolol under visible light - Yuehua Deng; Qianqian Che; Yani Li; Jiating Luo; Xiang Gao; Yan He; Yiling Liu; Tong Liu; Xiaolong Zhao; Xiaobin Hu; Wei Zhao (Journal of Environmental Sciences, 2024)

Circ_0090231 knockdown protects vascular smooth muscle cells from ox-LDL-induced proliferation, migration and invasion via miR-942-5p/PPM1B axis during atherosclerosis - Jian Yang; Xiangyan Li; Yuming Zhang; Pengfei Che; Wei Qin; Xuecui Wu; Yue Liu; Bing Hu (Molecular and Cellular Biochemistry, 2024)

Polystyrene microplastics enhance microcystin-LR-induced cardiovascular toxicity and oxidative stress in zebrafish embryos - Yuchun Xiao; Liwen Hu; Jiayao Duan; Huimin Che; Wenxin Wang; Yuan Yuan; Jiayi Xu; Daojun Chen; Sujuan Zhao (Environmental Pollution, 2024)

Correlation of gut microorganisms and non-volatile flavor substances provides new insights for breeding Scylla paramamosain - Gao Gao; Xing Li; Kangxiang Qin; Yun Hu; Xiaosong Jiang; Chenxi Che; Yuntao Li; Changkao Mu; Chunlin Wang; Huan Wang (Journal of Oceanology and Limnology, 2024)

Self-reconstructed ZIF-L/Co(OH)2 heterointerface modulates electronic structure of Ru and boosts electrocatalytic hydrogen evolution - Xinhui Yu; Yi Chen; Yuanyuan Wu; Xianyu Chu; Bo Liu; Bo Hu; Guangbo Che; Wei Jiang; Chunbo Liu (Chemical Engineering Journal, 2024)

A pilot restoration of Enhalus acoroides by transplanting dislodged rhizome fragments and its effect on the microbial diversity of submarine sediments - Hu Li; Jianguo Liu; Litao Zhang; Xingkai Che; Mengjie Zhang; Tie Zhang (Journal of Environmental Management, 2024)

Multifunctional Spirulina-hybrid helical microswimmers: Imaging and photothermal efficacy enabled by intracellular gold deposition - Ziqiao Li; Yanan Che; Ming Chen; Jing Hu; Pan He; Xiang Sun; Xiaozhen Wu; Youliang Yao; Huili Zheng; Gang Liu; Xiaohui Yan (Chemical Engineering Journal, 2024)

Key characteristics of new particle formation events occurring simultaneously in the Yangtze River Delta and northeast rural sites in China - Shuo Liu; Peng Wang; Qianli Ma; Xiaojing Shen; Hanqing Kang; Junying Sun; Quan Liu; Yangmei Zhang; Muzhen Shi; Dajiang Yu; Junting Zhong; Xinyao Hu; et al. (Atmospheric Environment, 2024)

Characterization of Organosulfates (OSs) in typical urban areas in Eastern China: Source, Process, and Volatility - Yang Du; Hanxiong Che; Zier Bao; Yiliang Liu; Qing Li; Miao Hu; Jiawei Zhou; Shumin Zhang; Xiaojiang Yao; Quan Shi; Chunmao Chen; Yan Han; et al. (Atmospheric Research, 2024)

Environmental sustainability assessment of a new food waste anaerobic digestion and pyrolysis hybridization system - Solomon Inalegwu Okopi; Jianfei Zeng; Xuetong Fan; Jiaxin Lu; Jiahao Cui; Yang Hu; Jiayu Wang; Jiaxin Chen; Oraléou Sangué Djandja; Yingqun Ma; Lei Che; Gu Zhaolin; et al. (Waste Management, 2024)

New insight into oxygen vacancy and synergism in CuCeOx catalysts based on the toluene oxidation - Guangtao Hu; Zirui Zhang; Chang’an Wang; Guojie Li; Dandan Zhou; Jinshi Wang; Defu Che; Running Kang (Journal of Environmental Chemical Engineering, 2024)

Surfeit Locus Protein 4 as a Novel Target for Therapeutic Intervention in Cerebral Ischemia–Reperfusion Injury - Wenjie Hu; Xiangyi Kong; Yu Cui; Hui Wang; Jingchen Gao; Xiyuran Wang; Shujun Chen; Xiaohua Li; Shifang Li; Fengyuan Che; Qi Wan (Molecular Neurobiology, 2024)

Storage and dynamics of soil organic carbon in allochthonous-dominated and nitrogen-limited natural and planted mangrove forests in southern Thailand - Jianxiong Hu; Siriporn Pradit; Pei Sun Loh; Zengxuan Chen; Chuanyi Guo; Thi Phuong Quynh Le; Chantha Oeurng; Ty Sok; Che Abd Rahim Mohamed; Choon Weng Lee; Chui Wei Bong; Xixi Lu; et al. (Marine Pollution Bulletin, 2024)

Common vetch intercropping with reduced irrigation ensures potato production by optimizing microbial interactions - Ting Che; Xinyue Zhang; Mingyue He; Fei Wang; Na Li; Xiayun Zang; Zhuoliang Xiao; Yuanzhou Xu; Feng Hu; Yongfeng Ren; Huijuan Zhang; Li Xu; et al. (Field Crops Research, 2024)

Detection of surface defects for maize seeds based on YOLOv5 - Yu Xia; Tianci Che; Jingwu Meng; Jinghao Hu; Gengle Qiao; Wenbo Liu; Jie Kang; Wei Tang (Journal of Stored Products Research, 2024)

Multi-sensor integrated mapping of global XCO2 from 2015 to 2021 with a local random forest model - Jiabin Chen; Ruohua Hu; Leyan Chen; Zihao Liao; Linlin Che; Tongwen Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Decoration of cyanamide groups to tune the surface electronic structures of semiconductor photocatalysts for efficient solar driven CO2 reduction - Kai Zhang; Xingjian Zhang; Chen Sun; Lei Gao; Zhiyi Huang; Qixiang Pian; Kunhong Che; Yueru Hu; Xiaokun Cui (Chemical Engineering Journal, 2024)

Experimental study and techno-economic analysis of co-processing system for treatment of food waste with various impurities - Solomon Inalegwu Okopi; Jiayu Wang; Wen Liang; Wenzhuo Kong; Yang Hu; Jiahao Cui; Xinyang Guo; Weiwei Zhao; Lei Che; Zhaolin Gu; Fuqing Xu (Bioresource Technology, 2024)

Significant influence of nitrate on light absorption enhancement of refractory black carbon in the winter of 2022 in Beijing - Xinyao Hu; Quan Liu; Yangmei Zhang; Xiaojing Shen; Jiayuan Lu; Aoyuan Yu; Shuo Liu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2024)

Size-resolved effective density of ambient aerosols measured by an AAC–SMPS tandem system in Beijing - Jiayuan Lu; Xiaojing Shen; Qianli Ma; Aoyuan Yu; Xinyao Hu; Yangmei Zhang; Quan Liu; Shuo Liu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2024)

Cracking and erosion behaviors of sand–clay mixtures stabilized with microbial biopolymer and palm fiber - Jin Liu; Zi Wang; Guochang Hu; Jian Xue; Fan Bu; Miao Jing; Zezhuo Song; Wenyue Che (Science of The Total Environment, 2023)

A study on photocatalytic Janus membrane reactor for direct conversion of low concentration carbon dioxide in air to methane: Effects of combination of two-dimensional carbon nanosheets - Chien-Chieh Hu; Ya-Chiao Chen; Eyasu Gebrie Ajebe; Meng-Che Tsai; Wei-Song Hung; Hsieh-Chih Tsai; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2023)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Relationship between night shift and sleep problems, risk of metabolic abnormalities of nurses: a 2 years follow-up retrospective analysis in the National Nurse Health Study (NNHS) - Heli Zhang; Jingpin Wang; Siwei Zhang; Sumei Tong; Jinping Hu; Ying Che; Lin Zhuo; Peng Wang; Rongmei Geng; Yujie Zhou; Panfeng Wang; Siyan Zhan; et al. (International Archives of Occupational and Environmental Health, 2023)
Background and purpose Efforts to improve nurses’ physical and mental health are critical to ensuring the safety and quality of the healthcare system. Long-term studies targeting the relevancy of nurses’ occupation characteristics with health conditions remain insufficient. This study aimed to examine the relationship between nurses’ night shift and sleep problems and metabolic abnormalities risk. Methods This study was a part of the National Nurse Health Study, an ambispective cohort study in China, in 2021. Based on an integration physical examination data system, this study carried out a retrospective analysis of 730 nurses from 2018 to 2020 and combined with a questionnaire survey in 2021. The STROBE guidelines were adopted for reporting. Results In the 23 (23.0, 24.0) months follow-up, higher night shift load was associated with more sleep problems such as shortened sleep duration, sleep disorders, poor sleep quality, and sleep deprivation. Moreover, night shift load was associated with chronic diseases risk factors, increasing body mass index and body fat, with more night shift density, increasing the occurrence of low levels of high-density lipoprotein cholesterol, high triglyceride, triglyceride/high-density lipoprotein cholesterol ratio, and serum uric acid. Conclusion The night shift load has become an occupational health concern, contributing to chronic diseases relevant metabolic risk factors and negative influence on sleep health. Focus on the strategies to improve the sleep quality of nurses undergoing night shift work, optimize work scheduling and ongoing monitor the relevant risk factors are essential to enhance the stability and well-being of the nursing workforce. Clinical Trials registration information: NCT04572347, on October 1, 2020. https://www.clinicaltrials.gov/ct2/show/NCT04572347

Impacts of climate change on herpetofauna diversity in the Qinghai‐Tibetan Plateau - Alex Plimo Karuno; Xue Mi; Youhua Chen; Da‐Hu Zou; Wei Gao; Bao‐Lin Zhang; Wei Xu; Jie‐Qiong Jin; Wen‐Jing Shen; Song Huang; Wei‐Wei Zhou; Jing Che (Conservation Biology, 2023)
Although numerous studies on the impacts of climate change on biodiversity have been published, only a handful are focused on the intraspecific level or consider population‐level models (separate models per population). We endeavored to fill this knowledge gap relative to the Qinghai‐Tibetan plateau (QTP) by combining species distribution modeling (SDMs) with population genetics (i.e., population‐level models) and phylogenetic methods (i.e., phylogenetic tree reconstruction and phylogenetic diversity analyses). We applied our models to 11 endemic and widely distributed herpetofauna species inhabiting high elevations in the QTP. We aimed to determine the influence of environmental heterogeneity on species’ responses to climate change, the magnitude of climate‐change impacts on intraspecific diversity, and the relationship between species range loss and intraspecific diversity losses under 2 shared socioeconomic pathways (SSP245 and SSP585) and 3 future periods (2050s, 2070s, and 2090s). The effects of global climatic change were more pronounced at the intraspecific level (22% of haplotypes lost and 36% of populations lost) than the morphospecies level in the SSP585 climate change scenario. Maintenance of genetic diversity was in general determined by a combination of factors including range changes, species genetic structure, and the part of the range predicted to be lost. This is owing to the fact that the loss and survival of populations were observed in species irrespective of the predicted range changes (contraction or expansion). In the southeast (mountainous regions), climate change had less of an effect on range size (>100% in 3 species) than in central and northern QTP plateau regions (range size

Rebuilding high-quality near-surface ozone data based on the combination of WRF-Chem model with a machine learning method to better estimate its impact on crop yields in the Beijing-Tianjin-Hebei region from 2014 to 2019 - Tian Han; Xiaomin Hu; Jing Zhang; Wenhao Xue; Yunfei Che; Xiaoqing Deng; Lihua Zhou (Environmental Pollution, 2023)

tDCS Regulates ASBT-3-OxoLCA-PLOD2-PTEN Signaling Pathway to Confer Neuroprotection Following Rat Cerebral Ischemia-Reperfusion Injury - Xiangyi Kong; Xujin Yao; Jinyang Ren; Jingchen Gao; Yu Cui; Jiangdong Sun; Xiangyu Xu; Wenjie Hu; Hui Wang; Huanting Li; Oleg O. Glebov; Fengyuan Che; et al. (Molecular Neurobiology, 2023)

Performance and mechanism of a novel biopolymer binder for clayey soil stabilization: Mechanical properties and microstructure characteristics - Jin Liu; Wenyue Che; Xiaowei Lan; Mengyuan Hu; Mengyao Qi; Zezhuo Song; Mengya Sun; Miao Jing; Wei Qian; Changqing Qi (Transportation Geotechnics, 2023)

Reforestation substantially changed the soil antibiotic resistome and its relationships with metal resistance genes, mobile genetic elements, and pathogens - Song Zhang; Ting Li; Jinming Hu; Kexin Li; Dong Liu; Haixia Li; Fang Wang; Danhong Chen; Zejin Zhang; Qiuping Fan; Xiaoyong Cui; Rongxiao Che (Journal of Environmental Management, 2023)

Gorgeous turn-back: Rough surface treatment strategy induces Cu-C and N-C active moieties for bifunctional oxygen electrocatalysis - Shuai Wang; Zhongmei Che; Min Zou; Yue Wu; Min Cui; Yingshu Guo; Mingrui Zhang; Wei Hu; Zihan Zou; Guangqiang Lv; Zexing Wu; Jeonghun Kim; et al. (Chemical Engineering Journal, 2023)

Electric-field control of reversible electronic and magnetic transitions in two-dimensional oxide monolayer magnets - Guopeng Wang; Tao Hu; Yimin Xiong; Xue Liu; Shengchun Shen; Jianlin Wang; Mengqian Che; Zhangzhang Cui; Yingying Zhang; Luyi Yang; Zhengcao Li; Yalin Lu; et al. (Science Bulletin, 2023)

Seed priming with rutin enhances tomato resistance against the whitefly Bemisia tabaci - Juan Tang; Haowei Shen; Rong Zhang; Fengbo Yang; Jinyu Hu; Jinting Che; Hongyan Dai; Hong Tong; Qingjun Wu; Youjun Zhang; Qi Su (Pesticide Biochemistry and Physiology, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Accelerating proton conduction in proton exchange membranes with sandwich structure based on carbon nanotubes oxide - Ke Liu; Shu Hu; Xiaoqing Wei; Tingting Zuo; Quantong Che (Process Safety and Environmental Protection, 2023)

Green waste and sewage sludge feeding ratio alters co-composting performance: Emphasis on the role of bacterial community during humification - Zejin Zhang; Changqun Duan; Yuxian Liu; Anning Li; Xi Hu; Jingkun Chen; Song Zhang; Xin Li; Rongxiao Che; Shiyu Li; Flemming Ekelund; Xiaoyong Cui (Bioresource Technology, 2023)

Seasonal variation of particle hygroscopicity and its impact on cloud-condensation nucleus activation in the Beijing urban area - Sinan Zhang; Xiaojing Shen; Junying Sun; Huizheng Che; Yangmei Zhang; Quan Liu; Can Xia; Xinyao Hu; Junting Zhong; Jialing Wang; Shuo Liu; Jiayuan Lu; et al. (Atmospheric Environment, 2023)

The degradation of subalpine meadows significantly changed the soil microbiome - Kaifang Liu; Ting Li; Xingwu Duan; Song Zhang; Meiping Chen; Haiyan Hou; Zelin Wang; Anlan Yu; Danhong Chen; Xiaoliang Zhang; Jinming Hu; Yifan Dong; et al. (Agriculture, Ecosystems & Environment, 2023)

Transcriptome profiling of unigenes participating in salt tolerance in purslane (Portulaca oleracea) under salinity stress - Hongmei Du; Shah Zaman; Shuiqingqing Hu; Shengquan Che (Acta Physiologiae Plantarum, 2023)

Boosting freshwater fish conservation with high‐resolution distribution mapping across a large territory - Juan Tao; Chengzhi Ding; Jinnan Chen; Liuyong Ding; Sébastien Brosse; Jani Heino; Virgilio Hermoso; Ruidong Wu; Ziwang Wang; Jiaxin Hu; Rongxiao Che; Xiaowei Jin; et al. (Conservation Biology, 2023)
The lack of high‐resolution distribution maps for freshwater species across large extents fundamentally challenges biodiversity conservation worldwide. We devised a simple framework to delineate the distributions of freshwater fishes in a high‐resolution drainage map based on stacked species distribution models and expert information. We applied this framework to the entire Chinese freshwater fish fauna (>1600 species) to examine high‐resolution biodiversity patterns and reveal potential conflicts between freshwater biodiversity and anthropogenic disturbances. The correlations between spatial patterns of biodiversity facets (species richness, endemicity, and phylogenetic diversity) were all significant ( r = 0.43–0.98, p

Simultaneous profiling of dust aerosol mass concentration and optical properties with polarized high-spectral-resolution lidar - Da Xiao; Nanchao Wang; Sijie Chen; Lingyun Wu; Detlef Müller; Igor Veselovskii; Chengcai Li; Eduardo Landulfo; Venkataraman Sivakumar; Jing Li; Huizheng Che; Jing Fang; et al. (Science of The Total Environment, 2023)

Highly anti-interference electrocatalytic sensing for dopamine with nitrogen-doped graphdiyne directly in biofluids - Min Cui; Peicheng Xin; Zhongmei Che; Min Zou; Mingrui Zhang; Xiaofeng Sun; Yanan Yuan; Zihan Zou; Guangqiang Lv; Shuai Wang; Wei Hu (Chemical Engineering Journal, 2023)

Decades of reforestation significantly change microbial necromass, glomalin, and their contributions to soil organic carbon - Mengling Zhang; Rongxiao Che; Zhibao Cheng; Hongkai Zhao; Chengwei Wu; Jinming Hu; Song Zhang; Dong Liu; Xiaoyong Cui; Yibo Wu (Agriculture, Ecosystems & Environment, 2023)

A reduced-form ensemble of short-term air quality forecasting with the Sparrow search algorithm and decomposition error correction - Kun Hu; Jinxing Che (Environmental Science and Pollution Research, 2023)

Soil sample sizes for DNA extraction substantially affect the examination of microbial diversity and co-occurrence patterns but not abundance - Ting Li; Song Zhang; Jinming Hu; Haiyan Hou; Kexin Li; Qiuping Fan; Fang Wang; Linfeng Li; Xiaoyong Cui; Dong Liu; Rongxiao Che (Soil Biology and Biochemistry, 2023)

The protective effect of Eleutheroside E against the mechanical barrier dysfunction triggered by lipopolysaccharide in IPEC-J2 cells - Huijuan Li; Rui Han; Feng Yong; Yueli Fan; Bao Zhao; Xiaocai Hu; Tianrui Zhang; Dongsheng Che (Research in Veterinary Science, 2023)

Hydrogenation of N-ethylcarbazole with Hydrogen-Methane mixtures for hydrogen storage - Hu Liu; Jingwen Xue; Pengfei Yu; Yankang Zhang; Jinhua Wang; Defu Che (Fuel, 2023)

Effect of high light and desiccation on photosystem II in the seedlings and mature plants of tropical seagrass Enhalus acoroides during low tide - Xingkai Che; Hu Li; Litao Zhang; Jianguo Liu (Journal of Oceanology and Limnology, 2023)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

UCRNet: Underwater color image restoration via a polarization-guided convolutional neural network - Haofeng Hu; Yizhao Huang; Xiaobo Li; Liubing Jiang; Li Che; Tiegen Liu; Jingsheng Zhai (Frontiers in Marine Science, 2022)
Underwater images always suffer from low contrast and color distortion due to the wavelength-dependent scattering and absorption effects caused by particles existing in turbid water, especially in high turbidity conditions. Based on the polarization properties of the backscattering light, polarimetric methods can estimate the intensity level of the backscattering and the transmittance of the media. Accordingly, they can separate the target signal from the undesired ones to achieve high-quality imaging. In addition, learning-based polarimetric methods are effective for gray-model image restoration, but the learning-based polarimetric technique for color image restoration has yet to be considered. In this paper, we propose a 3- dimensional convolutional neural network, which maintains the correlation of polarization information among different polarization channel images as well as embodies polarization constraints, for underwater color image restoration. The experimental results verify that the proposed solution improves the image quality (i.e., the image contrast, details, and color) and outperforms other existing methods, especially when the turbidity of scattering media is high. The proposed solution can be readily applied to practical applications and potentially realize the clear vision in other scattering media, including biomedical imaging and remote sensing.

Flame atomic absorption spectrometry combined with surface-modified magnetic mesoporous silica microspheres by polyethyleneimine for enrichment, isolation and determination of Cu 2+ in preserved eggs after high-temperature digestion - Zhengxiang Li; Tong Che; Minghong Yang; Xujia Hu (Food Additives & Contaminants: Part A, 2022)

Molecular characteristics and pathogenicity of an equid alphaherpesvirus 1 strain isolated in China - Yue Hu; Qinrui Jia; Jianhua Liu; Wencheng Sun; Zilei Bao; Chuanzhong Che; Guiling Wu; Bin Fan; Jarhen; Duoliang Ran (Virus Genes, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

POLLEN STERILITY, a novel suppressor of cell division, is required for timely tapetal programmed cell death in rice - Ronghui Che; Bin Hu; Wei Wang; Yunhua Xiao; Dapu Liu; Wenchao Yin; Hongning Tong; Chengcai Chu (Science China Life Sciences, 2022)

Distinct assembly mechanisms of microbial sub-communities with different rarity along the Nu River - Song Zhang; Kexin Li; Jinming Hu; Fang Wang; Danhong Chen; Zejin Zhang; Ting Li; Linfeng Li; Juan Tao; Dong Liu; Rongxiao Che (Journal of Soils and Sediments, 2022)

Nanotechnology advances in pathogen- and host-targeted antiviral delivery: multipronged therapeutic intervention for pandemic control - Kai-Chieh Yang; Jung-Chen Lin; Hsiao-Han Tsai; Chung-Yao Hsu; Vicky Shih; Che-Ming Jack Hu (Drug Delivery and Translational Research, 2021)

An approach for improving the NRLMSISE-00 model using a radiosonde at Golmud of the Tibetan Plateau - Yaru Dai; Weilin Pan; Xiong Hu; Zhixuan Bai; Chao Ban; Hengheng Zhang; Yunfei Che (Meteorology and Atmospheric Physics, 2020)

Increased litter input significantly changed the total and active microbial communities in degraded grassland soils - Rongxiao Che; Dong Liu; Jinling Qin; Fang Wang; Weijin Wang; Zhihong Xu; Linfeng Li; Jinming Hu; Iman Tahmasbian; Xiaoyong Cui (Journal of Soils and Sediments, 2020)

Research Progress on Estimation of the Atmospheric Boundary Layer Height - Hongsheng Zhang; Xiaoye Zhang; Qianhui Li; Xuhui Cai; Shaojia Fan; Yu Song; Fei Hu; Huizheng Che; Jiannong Quan; Ling Kang; Tong Zhu (Journal of Meteorological Research, 2020)

The auxin‐inducible phosphate transporter AsPT5 mediates phosphate transport and is indispensable for arbuscule formation in Chinese milk vetch at moderately high phosphate supply - Xiaoning Fan; Xianrong Che; Wenzhen Lai; Sijia Wang; Wentao Hu; Hui Chen; Bin Zhao; Ming Tang; Xianan Xie (Environmental Microbiology, 2020)
Summary Phosphorus is a macronutrient that is essential for plant survival. Most land plants have evolved the ability to form a mutualistic symbiosis with arbuscular mycorrhizal (AM) fungi, which enhances phosphate (Pi) acquisition. Modulation of Pi transporter systems is the master strategy used by mycorrhizal plants to adapt to ambient Pi concentrations. However, the specific functions of PHOSPHATE TRANSPORTER 1 ( PHT1 ) genes, which are Pi transporters that are responsive to high Pi availability, are largely unknown. Here, we report that AsPT5, an Astragalus sinicus (Chinese milk vetch) member of the PHT1 gene family, is conserved across dicotyledons and is constitutively expressed in a broad range of tissues independently of Pi supply, but is remarkably induced by indole‐3‐acetic acid (auxin) treatment under moderately high Pi conditions. Subcellular localization experiments indicated that AsPT5 localizes to the plasma membrane of plant cells. Using reverse genetics, we showed that AsPT5 not only mediates Pi transport and remodels root system architecture but is also essential for arbuscule formation in A . sinicus under moderately high Pi concentrations. Overall, our study provides insight into the function of AsPT5 in Pi transport, AM development and the cross‐talk between Pi nutrition and auxin signalling in mycorrhizal plants.

Synthesis and plant growth regulatory activities of 2′,3′-PhABA and iso-2′,3′-PhABA esters - Chuan Wan; Jiaqi Li; Fenghai Zhao; Dongyan Yang; Chuanliang Che; Shanshan Ding; Yimin Hu; Yumei Xiao; Zhaohai Qin (Molecular Diversity, 2020)

Optimization of air quality monitoring network based on a spatiotemporal-spectrum manifold analysis - Chi-Fang Wang; Ming-Che Hu; Chieh-Han Lee; Hwa-Lung Yu (Stochastic Environmental Research and Risk Assessment, 2019)

Development of Kriging-approximation simulated annealing optimization algorithm for parameters calibration of porous media flow model - Ming-Che Hu; Chia-Hui Shen; Shao-Yiu Hsu; Hwa-Lung Yu; Krzysztof Lamorski; Cezary Sławiński (Stochastic Environmental Research and Risk Assessment, 2019)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

Characterization and adsorption capacity of potassium permanganate used to modify activated carbon filter media for indoor formaldehyde removal - Shih-Cheng Hu; Ying-Chen Chen; Xin-Zhi Lin; Angus Shiue; Po-Hua Huang; Yen-Che Chen; Shu-Mei Chang; Chao-Heng Tseng; Bin Zhou (Environmental Science and Pollution Research, 2018)

Rainfall and inflow effects on soil erosion for hillslopes dominated by sheet erosion or rill erosion in the Chinese Mollisol region - Hai-ou Shen; Lei-lei Wen; Yun-feng He; Wei Hu; Hong-li Li; Xiao-cui Che; Xin Li (Journal of Mountain Science, 2018)

Stochastic competitive analysis of hydropower and water supplies within an energy–water nexus - Ming-Che Hu; Tailin Huang; Hwa-Lung Yu; Ching-Pin Tung (Stochastic Environmental Research and Risk Assessment, 2018)

Genome-wide DNA methylation analysis in jejunum of Sus scrofa with intrauterine growth restriction - Yue Hu; Liang Hu; Desheng Gong; Hanlin Lu; Yue Xuan; Ru Wang; De Wu; Daiwen Chen; Keying Zhang; Fei Gao; Lianqiang Che (Molecular Genetics and Genomics, 2018)

Silicon accumulated in the shoots results in down-regulation of phosphorus transporter gene expression and decrease of phosphorus uptake in rice - An Yong Hu; Jing Che; Ji Feng Shao; Kengo Yokosho; Xue Qiang Zhao; Ren Fang Shen; Jian Feng Ma (Plant and Soil, 2018)

Identification and validation of major QTLs and epistatic interactions for seed oil content in soybeans under multiple environments based on a high-density map - Qi Zhaoming; Zhang Xiaoying; Qi Huidong; Xin Dawei; Han Xue; Jiang Hongwei; Yin Zhengong; Zhang Zhanguo; Zhang Jinzhu; Zhu Rongsheng; Hu Zhenbang; Liu Chunyan; et al. (Euphytica, 2017)

Bioavailability of Cd and Zn in soils treated with biochars derived from tobacco stalk and dead pigs - Xing Yang; Kouping Lu; Kim McGrouther; Lei Che; Guotao Hu; Qiuyue Wang; Xingyuan Liu; Leilei Shen; Huagang Huang; Zhengqian Ye; Hailong Wang (Journal of Soils and Sediments, 2017)

The bioconcentration ability of heavy metal research for 50 kinds of rice under the same test conditions - Wen-Juan Xie; Lei Che; Guang-Yu Zhou; Li-Na Yang; Min-Yu Hu (Environmental Monitoring and Assessment, 2016)

Variability of Antarctic Intermediate Water south of Australia and its relationship with frontal waves - LinLin Zhang; XiaoMei Yan; Che Sun; DunXin Hu (Science China Earth Sciences, 2016)

Interactive effects of glutamine and gamma-aminobutyric acid on growth performance and skeletal muscle amino acid metabolism of 22–42-day-old broilers exposed to hot environment - Hong Hu; Xi Bai; Assar Ali Shah; Sifa Dai; Like Wang; Jinling Hua; Chuanyan Che; Shaojun He; Aiyou Wen; Jinpeng Jiang (International Journal of Biometeorology, 2016)

Release of soluble elements from biochars derived from various biomass feedstocks - Hailu Wu; Xiaodong Che; Zhuhong Ding; Xin Hu; Anne Elise Creamer; Hao Chen; Bin Gao (Environmental Science and Pollution Research, 2016)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Mapping of QTL conferring resistance to sharp eyespot (Rhizoctonia cerealis) in bread wheat at the adult plant growth stage - Jiang Chen; Guo Hui Li; Zi Yi Du; Wei Quan; Hu Yan Zhang; Ming Zhe Che; Zhen Wang; Zhong Jun Zhang (Theoretical and Applied Genetics, 2013)

Helicobacter pylori HP0876 is Dispensable for Heme–Iron Acquisition but Attenuates Bacterial Adherence to Gastric Epithelial Cells - Tao Liu; Yun Shi; Xiao-fei Liu; Ying Guo; Xu-hu Mao; Che Tan; Yuan Zhuang; Liu-sheng Peng; Jin-yu Zhang; Quan-ming Zou (Current Microbiology, 2012)

Erratum to: The Toxicological Effects in Brain of Mice Following Exposure to Cerium Chloride - Haiquan Zhao; Zhe Cheng; Jie Cheng; Renping Hu; Yi Che; Yaling Cui; Ling Wang; Fashui Hong (Biological Trace Element Research, 2012)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

The Toxicological Effects in Brain of Mice Following Exposure to Cerium Chloride - Haiquan Zha; Zhe Cheng; Jie Chen; Renping Hu; Yi Che; Yaling Cui; Ling Wang; Fashui Hong (Biological Trace Element Research, 2011)

Expression, purification, and activity assay of peptide deformylase from Escherichia coli and Staphylococcus aureus - Xuchun Che; Jinwei Hu; Lijuan Wang; Zhifeng Zhu; Qiong Xu; Junqiang Lv; Zheng Fu; Yajun Sun; Jia Sun; Gang Lin; Rong Lu; Zhi Yao (Molecular and Cellular Biochemistry, 2011)

On the intensity and type transition of land use at the basin scale using RS/GIS: a case study of the Hanjiang River Basin - Guangming Yu; Qun Zeng; Shan Yang; Limei Hu; Xiaowei Lin; Yi Che; Yuge Zheng (Environmental Monitoring and Assessment, 2010)

Study on the aerosol transmission of Hantaan virus - Che Fengxiang; Lu Jianchun; Meng Lingyin; Li Jingsong; Li Junbao; Tong Yongyi; Zhang Chaolong; Zhang Songle; Hu Qingxuan; Lui Mingxia (Aerobiologia, 1998)

Particle diameter of the airborne microorganisms over Beijing and Tianjin area - Che Fengxiang; Hu Qingxuan; Meng Lingying; Li Junbao (Aerobiologia, 1992)

Factors of influence on microbial pollution in the atmosphere over Beijing area - Che Fengxiang; Hu Qingxuang; Chen Zhensheng; Meng Lingyin; Yan Shigang (Aerobiologia, 1991)